Anatomical danger zone reconsidered: a micro‐CT study on dentine thickness in mandibular molars. (9th June 2019) - De‐Deus, G.; Rodrigues, E. A.; Belladonna, F. G.; Simões‐Carvalho, M.; Cavalcante, D. M.; Oliveira, D. S.; Souza, E. M.; Giorgi, K. A.; Versiani, M. A.; Lopes, R. T.; Silva, E. J. N. L.; Paciornik, S.
Abstract: Aim: To investigate the smallest dentine thickness in mesial canals of mandibular molars along the cervical and middle thirds of the root by means of a micro‐computed tomographic (micro‐CT) technology and digital image analysis. Methodology: Fifty mesial roots of mandibular molars having two independent canals (mesiobuccal and mesiolingual), in the coronal and middle levels, were selected and scanned in a micro‐CT device. After reconstruction procedures, approximately 468 slices per root covering the 7 mm below the furcation area of the mesial root were analysed to measure the smallest dentine thickness (danger zone [DZ]) in each slice from both distal and mesial regions of the mesial canals by an automatic segmentation process. Results: The DZ values in the mesiobuccal canals varied from 0.67 to 1.93 mm, with an average of 1.13 ± 0.21 mm. For the mesiolingual canals, the DZ varied from 0.77 to 1.89 mm with an average of 1.10 ± 0.21 mm. There was no correspondence in the DZ between the mesiobuccal and mesiolingual canals at the same cross‐sectional level in 71% of the specimens. Moreover, the smallest dentine thickness was towards the mesial region of the roots in 22% and 18% of the mesiolingual and mesiobuccal canals, respectively. (Figs 1 and 2 Conclusions: The smallest dentine thickness was on the mesial plane of the roots in about 40% of the canals. The vertical location of the DZ in relation to the furcation area was in the middle third of the root.